Uma abordagem para visualização da evolução de código morto em sistemas de software orientados a objetos - Bastos, Camila (2017)
The evolution is fundamental for the software to always meet the needs of their users. The comprehension of this evolution can be used to find the source of current problems or to obtain information that makes possible to predict future characteristics of the software. However, the increasing of information, functionality, pollution and the amount of dead code throughout evolution leaves the software more complex, making it difficult to comprehension. Thus, software visualization techniques have been used to represent the evolution of certain attributes of the software, facilitating the understanding of its evolutionary characteristics. Nevertheless, there are gaps in exploring these techniques to understand factors that contribute to increase the complexity throughout evolution, for example, the presence of dead code. Based on these factors, in this work the DCEVizz approach was proposed to identify and visualize dead code in the evolution of object oriented software. The purpose of this approach is to better understand the existence of dead code in software versions and their evolutionary characteristics. The analysis and understanding of dead code evolution can provide information to predict increases in this code, to enhance security in their elimination and to facilitate their identification in versions. The approach was implemented in a plug-in for Eclipse (DCEVizz Tool) and evaluated in two phases. In the first phase, a qualitative comparison of the dead code identified by DCEVizz Tool with the dead code identified by Understand tool was performed. This comparison showed that the detection technique used in DCEVizz Tool identified a greater amount of dead code than Understand in all the analyzed software. In the second phase of the evaluation, an experimental study was performed with a group of volunteers, who performed a set of activities using and not using the approach. The results of this study indicate that the use of DCEVizz increased precision and efficiency in the execution of the activities and facilitated the understanding of the evolution of the code.